TAMIL NADU CONTRACT FARMING: A CASE OF RICE SEED AND GHERKIN CULTIVATION - A. Durgadevi; DR. M. Rajeswari (CV. Radja Publika, 2023)
ABASTRACT In this essay, the performance of contract farming in Tamil Nadu is discussed. It contracts non-contract farming with contract farming for gherkins and rice seed. It demonstrates how the traits of farm households with contracts and those without contracts differ. The main challenges contract farmers encounter is determined to be late payments, credit issues, water shortages, and the inability to achieve quality standards. The concerned contracting firm typically shifts output to other farms and to other regions whenever productivity declines.